2013
DOI: 10.1097/igc.0b013e31828b15cb
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Radiation Therapy for Patients With Type II Endometrial Carcinoma

Abstract: In the current study of surgically staged patients with type II endometrial carcinoma International Federation of Gynecology and Obstetrics stages I and II, adjuvant radiation therapy with or without chemotherapy resulted in a significant improvement in recurrence-free and disease-specific survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In 2013, Yechieli et al studied the effect of adjuvant radiation in patients with early-stage type II (UPSC and UCCC) endometrial carcinoma. They showed that RT significantly improved PFS, and there was a trend toward improved 5-year OS regardless of the use of CT or not [11]. Later in 2020 and 2021, two studies suggested that vaginal brachytherapy associated with adjuvant chemotherapy may be a suitable option for patients with stage I UPSC who underwent surgical staging especially those with poor prognostic factors [12,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2013, Yechieli et al studied the effect of adjuvant radiation in patients with early-stage type II (UPSC and UCCC) endometrial carcinoma. They showed that RT significantly improved PFS, and there was a trend toward improved 5-year OS regardless of the use of CT or not [11]. Later in 2020 and 2021, two studies suggested that vaginal brachytherapy associated with adjuvant chemotherapy may be a suitable option for patients with stage I UPSC who underwent surgical staging especially those with poor prognostic factors [12,23].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the aggressiveness and the increased risk of recurrence for these subtypes, optimal adjuvant therapy remains controversial, and data on the subject are scarce due to the low number and the heterogenous retrospective cohorts [5,[7][8][9]. Consequently, some of these studies reached contradictory conclusions [10][11][12][13][14][15] and the international guidelines such as the National Comprehensive Cancer Network (NCCN) present substantial variability in the treatment options [16].…”
Section: Introductionmentioning
confidence: 99%